HUBUNGAN VULVA HYGIENE DAN PENGGUNAN KB DENGAN KEPUTIHAN PADA WANITA USIA SUBUR - Rika Handayani (Universitas Prima Indonesia, 2021)
Based on the initial survey from the results of interviews at the Ananda Primary Clinic of the 8 EFA respondents, 5 among them were women who experienced vaginal discharge with odor-itchy complaints, and there was a burning sensation in the vaginal area. The mother said not to do Vulva Hygiene and use family planning. While 3 of them said they did not have vaginal discharge, the mother also said that they did Vulva Hygiene and did not use family planning. The research objective was to determine the relationship between Vulva Hygiene and Family Planning Use and vaginal discharge in women of childbearing age couples (PUS). This type of research is an analytical survey, with a cross-sectional approach, the population in this study were all women of as many as 38 people, where samples were taken using an accidental sampling technique. The data collection technique is carried out by using primary data obtained from questionnaire data which is directly examined by the researcher. The results of the research-tested using the chi-square result obtained Vulva Hygiene with p-value (0.011) < (0.05) and use of family planning with p-value (0.001) < (0.05). The conclusion in this study is that there is a relationship between Vulva Hygiene and Family Planning Use and Leucorrhoea in Women of Fertile Age Couples (PUS) at Klinik Hj. Nani AM.keb Labuhanbatu. It is recommended that health workers provide accurate information to patients on how to do Vulva Hygiene properly and correctly.